NUTRITION ASSESSMENT FOR ALLERGIC DERMATITIS IN CHILDREN AT DIFFERENT AGES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2024)
Allergic pathology currently ranks first among the most common chronic diseases in childhood [3]. The prevalence of food allergy (FA) in the population is 1-2.5%, the highest frequency of this pathology is observed among children of the first 2 years - 6-8%, in older age groups its prevalence decreases and in adults it is about 2% [2]. According to WHO, about 30% of the world's population has some kind of allergic reaction or disease. Hereditary predisposition plays an important role in the development of allergic pathology, but it should be noted that genetic factors are unlikely to explain the increase in the frequency of immune disorders such as atonic reactions to environmental allergens. External factors leading to an increase in the incidence of PA include changes in diet in economically developed countries over the past decade, as well as environmental changes. It is assumed that the influence of the environment, including the microbial environment, especially during critical periods of life, can directly change the type of host immune response. Therefore, PA is considered today as a multifactorial pathology, in the occurrence and development of which a number of pathogenetic mechanisms, both genetic and environmental, play a role. All this leads to a variety of clinical forms of food allergies, determines the specific course of the disease in each specific case and leads to the need for a strictly individual approach to treatment, including diet therapy.